Human Exposure to Field Radiated by Vertical Dipole Antenna over a Lossy Half-Space using Analytical Approach - Enida Cero Dinarević; Dragan Poljak; Vicko Dorić (Journal of Communications Software and Systems, 2024)
The paper deals with an efficient procedure to study human exposure to vertical dipole antenna above a flat lossy half space. The closed form expressions for the corresponding irradiated electrical field are obtained assuming the sinusoidal and triangular current distribution along the antenna, respectively. The corresponding integral field expressions are evaluated by means of numerical integration and analytical procedures. The computations have been undertaken in the far field zone for various antenna parameters and compared to rigorous numerical model. Provided the field radiated from the vertical dipole is determined, whole body average Specific Absorption Rate (SARWB) is computed in a simple parallelepiped model of the human body and cylindrical model of the human body, respectively.